Situation report on Nepal’s agrifood systems: August 2023 - Kumar, A.; Palikhe, A.; Maharjan, N.K.; Adhikari, M.; Gupta, S.; Minot, Nicholas; Dorosh, Paul A.; Kishore, Avinash; Koirala, Pankaj; Krupnik, Timothy J. (CSISA and TAFSSA, 2023)
Inflation continues to drive moderately high food costs: In July of 2023, Nepal’s GDP projections were adjusted downward for 2023/24 (i.e., Nepali year 2080/81)1. Growth moderation in GDP is attributed to tighter monetary policy, which has led to higher interest rates. In addition, import restrictions have been imposed to manage declining foreign exchange reserves2. The annual inflation rate for the 12 months ending in July stood at 7.7 percent compared to 6.3 percent a year ago. Similarly, the cost of food and beverages increased by 2.5 percent compared to the previous month, while inflation for non-food items declined marginally. The increment in food cost is mainly contributed by 13.0, 42.0 and 12.8 percent rises in costs of vegetables, spices, and cereals, respectively. At the regional level, the highest inflation level of 3.4 percent in food and beverages was observed in the Terai region compared to the previous month. Persistence of high prices for cereals: The prices of cereals and their products increased by 12.8 percent in July 2023 compared to the previous year, mainly contributed by 37.8 and 18.5 percent rise in prices of wheat flour and coarse rice. Across provinces, the highest price rises in wheat flour were observed in Sudurpashchim province with 54.4 percent followed by Karnali Province with 24.7 percent. Such rise in cereal prices could limit consumers’ access to basic food commodities, especially for the poor, resulting in food insecurity and malnutrition. The persistent high price for cereals calls for the development of more efficient marketing systems and effective social safety net programs. However, the monthly increase in cereal price was1.0 percent when compared with the price of June 2023. Laborers continued to experience an increase in their real wage rate: The overall year-onyear change in agricultural labor wage rate showed a growth of 6.0 percent in July 2023. The change was higher for females (6.3 percent) compared to males (5.6 percent). However, the change in wage rate in July 2023 remained constant in comparison to the rate of previous month. The higher growth in female wage rate, if sustained, can reduce the wage gap between male and female laborers.